2020
DOI: 10.5194/tc-2019-333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is the Surface Mass Balance of Antarctica? An Intercomparison of Regional Climate Model Estimates

Abstract: Abstract. Antarctic ice sheet mass loss is currently equivalent to around 1 mm year−1 of global mean sea level rise. Most mass is lost due to sub-ice shelf melting and calving of icebergs. Ice sheet models of the Antarctic ice sheet have thus largely concentrated on parameterising sub-shelf and calving processes. However, surface mass balance (SMB) is also of crucial importance in controlling the stability and evolution of the vast Antarctic ice sheet. In this paper we compare the performance of five different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(90 citation statements)
references
References 57 publications
(83 reference statements)
4
83
3
Order By: Relevance
“…runoff (309 ± 80 Gt yr -1 ) are very similar to the GrSMBMIP ensemble averages (338 ± 111 Gt yr -1 and 331 ± 102 Gt yr -1 , respectively). Comparison with an accompanying Antarctic model ensemble results suggests that our AIS SMB estimate for grounded and floating ice is larger than most models: Mottram et al (2020) found the ensemble mean of AIS SMB of 2486 Gt yr -1 (range: 2031-2757 Gt yr -1 ), which is less than our estimate of 2623 Gt yr -1 . We note, however, that the evaluation in Mottram et al (2020) of each model against observations suggests they each contain a negative bias (i.e., the modeled SMB is typically less than the observed).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…runoff (309 ± 80 Gt yr -1 ) are very similar to the GrSMBMIP ensemble averages (338 ± 111 Gt yr -1 and 331 ± 102 Gt yr -1 , respectively). Comparison with an accompanying Antarctic model ensemble results suggests that our AIS SMB estimate for grounded and floating ice is larger than most models: Mottram et al (2020) found the ensemble mean of AIS SMB of 2486 Gt yr -1 (range: 2031-2757 Gt yr -1 ), which is less than our estimate of 2623 Gt yr -1 . We note, however, that the evaluation in Mottram et al (2020) of each model against observations suggests they each contain a negative bias (i.e., the modeled SMB is typically less than the observed).…”
Section: Discussioncontrasting
confidence: 82%
“…Comparison with an accompanying Antarctic model ensemble results suggests that our AIS SMB estimate for grounded and floating ice is larger than most models: Mottram et al (2020) found the ensemble mean of AIS SMB of 2486 Gt yr -1 (range: 2031-2757 Gt yr -1 ), which is less than our estimate of 2623 Gt yr -1 . We note, however, that the evaluation in Mottram et al (2020) of each model against observations suggests they each contain a negative bias (i.e., the modeled SMB is typically less than the observed). Future evaluation of the MERRA-2 and GSFC-FDM SMB against observations will help assess whether its performance is degraded as compared to the ensemble presented in Mottram et al (2020).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The base image is a mosaicked RGB Sentinel-2 image of the Nivlisen Ice Shelf acquired on 26 January 2017. The solid black line marks the grounding line, according to the NASA Making Earth System Data Records for Use in Research Environments (MEaSUREs) Antarctic boundaries dataset (Mouginot et al, 2017). The solid blue line represents the blue ice areas in the region according to Hui et al (2014).…”
Section: Landsatmentioning
confidence: 99%
“…The simulations are called MAR(ACCESS1.3), MAR(CESM2), MAR(CNRM-CM6-1), and MAR(NorESM1-M) hereafter. We used the same intermediate spatial resolution (35 km) as in (Agosta et al, 2019) and (Mottram et al, 2020) 2015, Barthel et al (2020), and Agosta et al (in preparation). This highlights the importance of selecting ESMs that correctly represent the historical climate around Antarctica as they strongly controls present biases independently of the capacity of the RCM to improve ESMs results.…”
Section: Methodsmentioning
confidence: 99%